Estimating Health Care Cost Savings from an Educational Intervention to Prevent Bleeding‐Related Complications: The Outcomes Impact Analysis Model. Issue 1 (April 2014) - Ravyn, Dana; Ravyn, Vipa; Lowney, Rob; Ferraris, Victor
<x xml:space="preserve">Abstract</x> Introduction Investments in continuing medical education (CME) exceed $2 billion annually, but few studies report the economic impact of CME activities. Analysis of patient‐level economic outcomes data is often not feasible. Accordingly, we developed a model to illustrate estimation of the potential economic impact associated with CME activity outcomes. Methods Outcomes impact analysis demonstrated how costs averted from a CME symposium that promoted prevention of bleeding‐related complications (BRC) and reoperation for bleeding (RFB) in cardiac and thoracic operations could be estimated. Model parameter estimates were from published studies of costs associated with BRC and RFB. Operative volume estimates came from the Society of Thoracic Surgeons workforce data. The base case predicted 3 in 10 participants preventing one BRC or RFB in 2% or 1.5% of annual operations, respectively. Probabilistic sensitivity analysis (PSA) evaluated the effect of parameter uncertainty. Results 92% of participants (n = 133) self‐reported commitment to change, a validated measure of behavior change. For BRC, estimates for costs averted were $1, 502, 769 (95% confidence interval [CI], $869, 860–$2, 359, 068) for cardiac operations and $2, 715, 246 (95% CI, $1, 590, 308–$4, 217, 092) for thoracic operations. For RFB, the savings estimates were $2, 233, 988 (95% CI, $1, 223, 901–$3, 648, 719). Discussion Our economic model demonstrates that application of CME‐related learning to prevent bleeding complications may yield substantial cost savings. Model prediction of averted costs associated with CME allows estimation of the economic impact on outcomes in the absence of patient‐level outcomes data related to CME activities.